Art project to Kiev hills " Fictitious Gallery Expedition " as a unique declaration of freedom of artistic practice - Konovalova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article is dedicated to analysis of the Kiev artists' art project "Fiction Gallery Expedition" ("FGE"). The purpose of the article is to reveal the essence of understanding the artistic creativity freedom by summarizing the results of art review and by studying existence of objects in society. Relevance of the study is in presentation of poorly studied phenomenon of Kiev artistic sphere of the end of XX and beginning of the ХХI century. Study of the question of creativity freedom will reveal the distinction between bias of the contemporary artist and occasional manifestations of freedom, teetering on the edge of legality. The concept of "artistic freedom" in art has almost always been regulated by certain conditions, starting with the exhibition space and ending with social, moral and ethical laws. In this study, the author finds no limits of creativity determined by the courage, deep intuition of the artistic nature, rational and audacious embodiment of design into the unique landscape of Kiev.